A rare case of gastric cancer with bilateral breast metastasis during pregnancy - MEMİŞOĞLU, ASLI; DANE, FAYSAL; DEMİRCAN, NAZIM CAN; YUMUK, PERRAN FULDEN; ARIKAN, RUKİYE; ÖZGÜVEN, SALİH; SOYSAL, SUAH; BAŞOĞLU TÜYLÜ, TUĞBA; AKIN TELLİ, TUĞBA (SAGE PUBLICATIONS LTD, 2021)
Background Gastric cancer is rare during pregnancy and often diagnosed at a later stage due to overlapping symptoms of pregnancy. Breast metastasis of gastric cancer is another uncommon entity. We present a rare case of breast metastasis of gastric cancer during pregnancy. Case report A 26-year-old female was diagnosed with gastric cancer at 14 weeks of gestation and underwent total gastrectomy. She rejected adjuvant chemotherapy and continued pregnancy without any follow-up. Cancer recurred in bilateral breasts at 34th week of gestation mimicking primary inflammatory breast cancer. Management and outcome It was difficult to diagnose breast metastasis during pregnancy because of overlapping pregnancy symptoms. Following an unresponsive period to antibiotherapy, a fine needle biopsy on breast was performed and signet cell adenocarcinoma metastasis was determined. We started chemotherapy after delivery. There was a near complete response after first line of chemotherapy. Unfortunately, cancer was relapsed within three months and we started second-line chemotherapy. Discussion To our knowledge, this is the fourth case reported in medical literature of gastric cancer presented with breast metastasis during pregnancy. We will try to draw attention to diagnosis, treatment and different presentation of gastric cancer during pregnancy with review of the literature.
Keywords: Gastric cancer; pregnancy; breast; metastasis; case report; ADENOCARCINOMA